2020
DOI: 10.3389/fpsyg.2020.01023
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Hope in South Africa: A Population-Based Study

Abstract: A growing body of research has provided evidence for the cognitive motivational construct of hope as a psychological strength, particularly for children in adverse social circumstances. In children, hope is defined as a set of cognitions focused on children's agency to contemplate workable goals, to identify pathways to achieve those goals and the intrinsic beliefs about their capacity to activate sustained movement toward those goals. Using data from the third wave of the Children's Worlds International Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
2
9
2
Order By: Relevance
“…The scale authors further established satisfactory test-retest reliability of .71-.73 (Snyder et al, 1997). Validation studies of the CHS in the South African context by Savahl et al (2016), Guse et al (2016), Manuel et al (2020), and Savahl (2020) have also demonstrated acceptable reliability coefficients of .82, .73, .86 and .80 respectively.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…The scale authors further established satisfactory test-retest reliability of .71-.73 (Snyder et al, 1997). Validation studies of the CHS in the South African context by Savahl et al (2016), Guse et al (2016), Manuel et al (2020), and Savahl (2020) have also demonstrated acceptable reliability coefficients of .82, .73, .86 and .80 respectively.…”
Section: Introductionmentioning
confidence: 80%
“…In children, Hope Theory is premised on the notion that goal-directed hopeful thinking develops in the formative years and is a requisite for the child's development and survival (Savahl, 2020). Children's perceptions and evaluations of their capacity to activate resources to respond to challenges and barriers are important considerations for hope in children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most devastating effects of apartheid on the psychological well‐being of children and adolescents is the destruction of the “self”—an effect that is transmitted across generations (Benninger & Savahl, 2017). This manifested as a degeneration of the self‐concept, self‐esteem, hope for the future, optimism and aspirations (Savahl, 2020).…”
Section: Introductionmentioning
confidence: 99%